Classification and management of the midfoot Charcot diabetic foot. Issue 1 (February 2023) - Najefi, Ali-Asgar; Brown, Rick; Loizou, Constantinos
Abstract: Charcot neuroarthropathy adversely affects the quality of life of diabetic patients with peripheral neuropathy and therefore early diagnosis is essential. The midfoot is the commonest site for Charcot deformity and can lead to ulceration, deep infection and amputation. The goal of treatment in Charcot arthropathy is to achieve a stable, plantigrade foot without infection and ulceration to allow for ambulation in the long term. The aim of this article is to review the classification of Charcot midfoot deformity and assess the role of non-operative and surgical measures in the management of these patients. We specifically reviewed the indications and literature around surgical exostectomy.